A reliable and fast hydrogen gas leakage detector based on irreversible cracking of decorated palladium nanolayer upon aligned polymer fibers. (5th January 2015) - Chen, Ran; Ruan, Xiaodong; Liu, Weiting; Stefanini, Cesare
Abstract: A reliable fast response and non-maintenance hydrogen gas sensor is presented, which can be easily fabricated through sputtering palladium nanolayer onto uniaxially aligned electrospun polyurethane nanofibers. The designated palladium sensing nanolayer undergoes an irreversible cracking while being exposed to hydrogen gas, which induces a great resistance increases. Efficient and credible fabrication is investigated through a designed electrospinning device and the sensors show highly reliable response with good consistency. It has been shown that the sensor can detect hydrogen gas concentration as low as 20 ppm with response time less than 60 s and maximum relative resistance variance more than 70%. With its low-cost and easy-fabrication characteristics, this simplified nanofiber sensor provides an efficient and low cost solution for hydrogen leakage detection at scenarios where fast response, low concentration and room temperature working are essentially required. Highlights: We design a reliable and fast hydrogen gas leakage detector. This sensor is based on the irreversible cracking of palladium nanolayer. We design an easy and low-cost fabrication method. This sensor is tested to be fast and reliable. This sensor can work as non-maintenance reusable alarm device.